REVITALISASI BADAN LAYANAN UMUM PADA RUMAH SAKIT UMUM DAERAH LABUANG BAJI MAKASSAR MENGGUNAKAN METODE BALANCED SCORECARD - Nurfadillah, Rezki; Islamiah, Farida; Asmirani, Sri (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to evaluate the financial and non-financial performance of Labuang Baji Regional General Hospital (RSUD Labuang Baji) in Makassar before and after its transition to a Public Service Agency (BLU/BLUD). The hospital serves as the research object, with a four-year observation period from 2011 to 2014. The years 2011 and 2012 represent the period before becoming a Public Service Agency, while 2013 and 2014 represent the period after the transition. This research is a qualitative descriptive study using a case study approach. Data analysis was carried out using the Balanced Scorecard method, with data collection strategies including data triangulation, methodological triangulation, and theoretical triangulation. In general, there were no significant differences in strategic approaches before and after becoming a BLU/BLUD, except for differences in the percentage of targets to be achieved. The findings indicate that the performance of RSUD Labuang Baji improved following its transformation into a Public Service Agency. Financial performance exceeded target expectations, and most non-financial performance indicators also improved and met the established targets. These improvements are reflected in the performance scale results: prior to becoming a BLU/BLUD, the hospital’s performance was rated as "fair" with an average score of 0.40. After the transformation, the performance improved to a "good" category with an average score of 0.67